RADEC vs PjBL: Adding make-a-match media to enhance students' creative thinking skills - Khaerunnisa Khaerunnisa; Nanang Rahman; Haifaturrahmah Haifaturrahmah; Emese K. Nagy (Journal of Research in Instructional, 2025)
This study focuses on the comparative analysis of the effectiveness of the Read, Answer, Discuss, Explain, and Create (RADEC) and the Project-Based Learning (PjBL) models equipped with make-a-match media on the creative thinking skills of elementary school students. This study used a quasi-experimental research design with a pre-test and post-test group design. The research sample consisted of 52 fifth-grade students divided into two classes, each consisting of 26 students. Data were collected using a test. The paired t-test was used to calculate data, and N-gain calculations were used to measure the level of effectiveness. The results showed that both groups using the RADEC model (sig. = 0.001 <0.05) and PjBL (sig. 0.000 <0.05) demonstrated an effect on improving students' creative thinking skills before and after learning. However, the N-gain value indicates that RADEC reached 12.19% (ineffective category) with a mean post-test of 59.85, while PjBL reached 45.3% (less effective) with a mean post-test of 70.12. The findings indicate that PjBL with make-a-match media is more effective in improving students' creative thinking skills than RADEC with make-a-match media. Although the RADEC model also contributes to developing students' thinking skills, its impact on creativity is not as great as the PjBL model. This study provides valuable insights for educators and policymakers by highlighting the effectiveness of this learning approach. It suggests applying the PjBL model to develop students' creative potential further.